Assessment of quality of life of climacteric women using the Cervantes scale. Influence of ethnicity - Mercado-Lara, María Fernanda (2018)
Introduction: Quality of life and severity of menopausal symptoms vary among different population groups. Objective: To compare the quality of life of Colombian climacteric women belonging to two ethnic groups by using the Cervantes scale. Methods: Cross-sectional study of the CAVIMEC (Calidad de Vida en la Menopausia y Etnias Colombianas) research project, which administers a questionnaire of sociodemographic characteristics and the Cervantes scale to Hispanic and Afrodescendant women, 40 to 59 years old, living in populations of the Colombian Caribbean and Pacific. Door-to-door assessment by interviewers, risk-free research, performed with the approval of the ethics committee. We used Epi-Info 7 for data analysis. Unadjusted logistic regression was performed and comparisons were statistically significant if p <0.05. Results: We studied 1 894 women, 34.1% Afrodescendants and 65.9% Hispanics, aged 48.7 ± 5.7 and 48.2 ± 5.8, respectively. Hispanics had a higher psychological, sexual, aging and couple relationship deterioration, and less vasomotor symptoms than Afro-descendants, p <0.05. The Cervantes Scale score was 39.2 ± 22.6 in Afrodescendants and 43.7 ± 25.0 in Hispanic women, p <0.001. Being Hispanic was associated with a 43% greater deterioration of the quality of life compared with Afro-descendants and was associated to “higher severity” in three domains: menopause / health OR: 1.40 [95% CI: 1.05-1.85], sexuality OR: 1.46 [IC05%: 1.19-1.80] and couple relationship OR: 1.36 [95% CI: 1.10-1.69]. Conclusions: There were significant differences in the deterioration of quality of life in the Colombian Hispanic and Colombian Afro-descendant women studied.